Clark's Malthus delusion: response to 'Farming in England 1200–1800'1. (27th December 2017) - Broadberry, Stephen; Campbell, Bruce M. S.; Klein, Alexander; Overton, Mark; van Leeuwen, Bas
Abstract: Clark's claims about the scale of English agricultural output from the 1200s to the 1860s flout historical and geographical reality. His income‐based estimates start with the daily real wages of adult males and assume that days worked per year were constant. Those advanced in British economic growth make no such assumption and instead are built up from the output side. They correlate better with population trends and are consistent with an economy slowly growing and becoming richer. Clark's denial that such growth occurred, his assertion that substantially more land must have been under arable cultivation, his belief that conditions of full employment invariably prevailed in the countryside at harvest time, his concern that the wage bill would have exceeded the value of output in British economic growth, his refusal to consider the possibility that the working year was of variable length, and his assertion that output per acre must have been equalized across arable and pasture are all shown to be figments of his 'Malthus delusion'.